Analysis of Global Warming Potential in Tofu Industry (Case Study: Industry X, Gresik) - Ekki Rahmawati; Shinfi Wazna Auvaria; Sulistiya Nengse; Yusrianti Yusrianti; Teguh Taruna Utama (Fakultas Teknik, 2022)
Tofu industry is one of the many SMEs operating in Indonesia. These industrial activities have the potential to have an impact on the environment. Industry X, Gresik has an average production capacity of 600-900 kg of tofu every day. The main energy used to produce tofu is firewood. The average daily use of firewood in this industry is 1,520 kg. Burning wood has the potential to cause global warming. In addition, this industry also does not manage its liquid waste which has the potential to cause pollution in aquatic ecosystems. The purpose of this research is to analyze the potential environmental impact of the tofu production process. Data collection methods include observation, interviews, and direct measurement. Data analysis using Life Cycle Assessment method and SimaPro 9.4 Software. Environmental impact assessment using the CML-IA (baseline) method. Based on the results of Simapro analysis, the global warming potential impact is 2,95 x 108 kgCO2-eq